Towards advanced Intellectual property management - Events and stages during the development. Evidence from the biotech sector - Frank Tietze; Ove Granstrand; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
During recent years the management of Intellectual Property (IP) underwent major changes. IP management systems became increasingly complex nowadays actively handling an integrated mix of intellectual assets rather than just administrating patents or trademarks as single, independently treated assets. Our paper describes and analyses the historic development of IP management in German and Swedish Dedicated Biotechnology Firms (DBFs) with our main focus on the following two issues: (1) Which events trigger the development towards an advanced IP management? (2) Can distinctive stages be identified in the development of IP management systems and if yes, how are they characterised? Our study draws primarily on 12 personal interviews with leading managers from six larger German and Swedish DBFs with rich experience in IP management that were founded between 1984 and 1997. During our study we found that shifts towards an advanced IP management were triggered by single crucial events (e.g. litigation) or an accumulated sum of incremental events, of either internal or external nature. Up to four different stages of IP management were found throughout the development of the case companies, while six criteria were identified that can be applied to characterize an IP management stage.
Keywords: 650; Intellectual Property Management; Dedicated Biotechnology Firm; Germany; Sweden